Análise de confiabilidade em modelos de bielas e tirantes - Santos, Victor Mark Pontes dos (2013)
This work explores the use of reliability techniques for selecting strut and tie models and explores the use of topology optimization techniques to generate these models automatically. A literature review is presented exploring probability concepts useful in reliability analysis, concepts about classic approaches to generate strut and topology optimization. The formulation is based on concepts of the limit analysis thus they are the theoretical basis of the strut and tie model. Formulations used in reliability analysis are presented, such as the Monte Carlo simulation and the methods FOSM and FORM. These techniques are applied in nine numerical applications. The first two examples explore alternative techniques on the topology optimization field so as enable appropriate strut and tie results consistent with the project of concrete structures. The following examples are used to validate the tools used in the reliability analysis and in the limit analysis. Finally the four following examples apply reliability analysis with failure function based on limit analysis to compare classic models with those obtained by using topology optimization and analyze the security level of the models with respect to changes in concrete strength, reinforcement provided by the ties and thickness of the struts.